Methylation profiling RIN3 and MEF2C identifies epigenetic marks associated with sporadic early onset Alzheimer’s disease - Boden, Kirsty A.; Barber, Imelda S.; Clement, Naomi; Patel, Tulsi; Guetta-Baranes, Tamar; Brookes, Keeley; Chappell, Sally; Craigon, Jim; Chapman, Natalie H.; Morgan, Kevin; Seymour, Graham B.; Bottley, Andrew (IOS Press, 2017)
A number of genetic loci associate with early onset Alzheimer’s disease (EOAD), however the drivers of this disease remains enigmatic. Genome wide association and in-vivo modelling have shown that loss-of-function e.g. ABCA7, reduced levels of SIRT1, MEFF2C or increases levels of PTK2β confer risk or link to the pathogenies. It is known that DNA methylation can profoundly affect gene expression and can impact on the composition of the proteome, therefore the aim of this study is to assess if genes associated with sporadic EOAD are differentially methylated. Epi-profiles of DNA extracted from blood and cortex were compared using a pyrosequencing platform. We identified significant group-wide hypomethylation in AD blood when compared to controls for 7 CpGs located within the 3’UTR of RIN3 (CpG1 P=0.019, CpG2 p=0.018, CpG3 p=0.012, CpG4 p=0.009, CpG5 p=0.002, CpG6 p=0.018 and CpG7 p=0.013 respectively; AD / Control n=22 / 26; Male / Female, 27 / 21). Observed effects were not gender specific. No group wide significant differences were found in the promoter methylation of PTK2β, ABCA7, SIRT1 or MEF2C, genes known to associate with LOAD. A rare and significant difference in methylation was observed for one CpG located upstream of the MEF2C promoter in one AD individual only (22% reduction in methylation, p=2.0E-10; Control n=26, AD n=25, Male / Female n=29 / 22). It is plausible aberrant methylation may mark sEOAD in blood and may manifest in some individuals as rare epi-variants for genes linked to sEOAD.